Khat (Catha edulis Forsk.) Dependence Potential and Pattern of Use in Saudi Arabia. (24th August 2015) - Abdelwahab, Siddig Ibrahim; Alsanosy, Rashad Mohammed; Rahim, Bahaa-eldin E. A.; Mohan, Syam; Taha, Sara; Mohamed Elhassan, Manal; El-Setouhy, Maged
Abstract : Background . Catha edulis Forsk. (Khat) is used for its psychoactive effects among people in Africa and the Arabian Peninsula, although its utilization is illegal in some countries such as Saudi Arabia. This study examined the pattern of Khat use and assessed the applicability of the Drug Abuse Screening Test-10 (DAST-10) to measure Khat dependence. Methods . A pretested questionnaire was used to gather data from 603 respondents. Variables included demographic characteristics, pattern of use, reasons for Khat chewing, and DAST-10. Stepwise-logistic regression was used to explore predictors of Khat dependence. Results . The majority of the respondents were married, had a secondary school level of education, were employed, were younger than 35 years old, and were living in rural areas. Many chewers gave more than one reason for using Khat. It was mainly used to increase mental capacity, physical strength, and social entertainment, as well as enhance cheerfulness and orgasms. Statistical modeling of Khat dependence suggested that the most significant predictors were residence (OR = 1.67, P < 0.02 ), frequency of Khat chewing (OR = 4.8, P < 0.01 ), age of starting Khat chewing (OR = 1.15, P < 0.01 ), and time of Khat effect (OR = 1.15, P < 0.04 ). Conclusion . Our study provides important information on the pattern of Khat use and its potential to cause dependence.